Aesthetics of Law and Dharma: Literary Artistry and Figurative Language in the Dharamshastra Scripture - Saengpetch Narueng, Sikharin (ARU Research Journal Humanities and Social Sciences, 2026)
This academic article aims to analyze the linguistic aesthetics found in the Dharamshastra of the Law of the Three Seals, with particular emphasis on literary artistry and figurative language as important means of communicating legal principles and ethical values in premodern Thai society. The Dharamshastra was not merely a body of legal provisions intended to uphold justice in practice; it also functioned as a form of “cosmic constitution,” meticulously constructed through sophisticated literary techniques. In a historical context in which law enforcement mechanisms were less complex than those of the modern state, language served as a principal means of establishing legitimacy, while literary artistry transformed law from a set of commands into a form of spiritual and ethical practice. For judicial authorities, adjudication was therefore represented not simply as a secular responsibility, but also as an act associated with the accumulation of merit, adherence to the natural and moral order, and the consequences of violating that order, which could affect both honor and decline. The analysis reveals that the integration of attha, understood as the underlying intention and meaning of justice, and dhamma, understood as the principles of natural and moral order, is conveyed through distinctive aesthetic features that bridge the world of legal discourse and the realm of ethical concepts. Figurative devices, including simile and symbolism, are employed not merely for rhetorical beauty but also to construct conceptual imagery through which those exercising judicial authority can apprehend the deeper meaning of attha-dhamma at both intellectual and spiritual levels. The study demonstrates that literary artistry plays a significant role in establishing the sacred authority of law and in sustaining the reverence and legitimacy accorded to premodern Thai legal traditions over time, thereby revealing how language, law, morality, and cosmological belief were interwoven in the construction and preservation of legal authority in premodern Thai society.